HIDUP SEBAGAI ORANG-ORANG ARIF SUATU TAFSIRAN TERHADAP EFESUS 5:15 - 21 - Tony Suhartono; Andre Djaafar; Suhendra Suhendra (JURNAL IMPARTA, 2023)
In the era of digital 4.0, where technology advances rapidly, many people seek to do everything quickly. This phenomenon also affects Christians, who aspire to embody the teachings of the Bible, but often wish to skip the process of growth and transformation. However, it is through the experiences and events of life that individuals are meant to undergo character development, becoming wise individuals rather than the opposite, becoming "foolish." Through this scholarly work, the author aims to encourage Christians to become wise individuals, meaning individuals who have the ability to apply their knowledge as children of light (children of God) in their behavior and actions. Believers should be capable of embracing opportunities to align their behavior with divine purposes, understanding and discerning the will of God, and allowing their lives to be completely guided by the Holy Spirit. The fulfillment of the Holy Spirit in the lives of believers is reflected in their songs, which serve as a means of exhortation and admonition to one another, offering praises directed towards the Lord. They express gratitude to God the Father through Jesus Christ and willingly submit to one another in an atmosphere of deep respect that emanates from sincere hearts towards Jesus Christ. The author employs methods such as textual analysis (Biblical verses), synthesis, addressing research inquiries, and reflecting on life experiences to accomplish these objectives